2005
DOI: 10.1080/13556210500353020
|View full text |Cite
|
Sign up to set email alerts
|

Khat (Catha edulis)—an updated review

Abstract: The habit of chewing fresh leaves and twigs of khat (Catha edulis) for their stimulating amphetamine-like effects is highly prevalent in East Africa and southwest on the Arabic peninsula. There is an extensive literature on khat providing information about its history, botany, production, geographical distribution, chemistry and pharmacology, and exploring the social, economic, medical, psychological and oral aspects related to its use. Some of this literature dates as early as the 11th century; however, most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
186
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(204 citation statements)
references
References 77 publications
7
186
0
2
Order By: Relevance
“…Moreover, khat is also reported as a risk factor for poor working memory 24-26, poor academic performance 27,28 , reduced productivity and increased daily financial expenditure 29 . Despite these harmful consequences, the cultivation and use of khat is on arise especially in Yemen, Arabian peninsula, East Africa, and Ethiopia in particular 30,31 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, khat is also reported as a risk factor for poor working memory 24-26, poor academic performance 27,28 , reduced productivity and increased daily financial expenditure 29 . Despite these harmful consequences, the cultivation and use of khat is on arise especially in Yemen, Arabian peninsula, East Africa, and Ethiopia in particular 30,31 .…”
Section: Introductionmentioning
confidence: 99%
“…The khat plant is known by a variety of names, such as qat in Yemen, chat in Ethiopia, jaad in Somalia and miraa in Kenya and Tanzania. Other names are marungi, catha, cat, gaad, African salad, tohai, bushman's tea, and flower of paradise; in most western literature it is referred to as khat (Baasher, 1980;Al-Hebshi & Skaug, 2005;Elmi, 1983;National Drug Intelligence Center, 2007).…”
mentioning
confidence: 99%
“…Interestingly, studies have also reported a strong association between khat chewing habit and high educafigure 1. Young khat shrub tional level (Alem, Kebede & Kullgren, 2007;Al-Hebshi, & Skaug, 2005). Many studies (Ihunwo, Kayanja & Amadi-Ihunwo, 2004;Ayana, Sherief & Tekli, 2002;Zein, 1983) have reported the use of khat by college and university students and proposed that the reasons for chewing by students are to get mental alertness, to work hard in their academic endeavors and to get good grades, though not all studies agree with these reasons (Mekonnen, Makonnen & Gebre-Tsadik, 1998).…”
mentioning
confidence: 99%
“…Chez 5 volontaires sains mâchant pour la première fois 60 grammes de khat frais, le pic plasmatique est atteint en 1,5 à 3,5 heures [23]. La concentration sanguine en cathinone se situe alors entre 40 et 140 ng/mL.…”
Section: Pharmacologieunclassified